Navigating Translation Challenges: a Holistic Examination of Common Issues Faced by Translation Learner in the Fifth Semester in Pertiwi University - Zaviena Juherni; Sahril Mujani; Susiyati Susiyati (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This study explores the challenges faced by fifth-semester translation students at Pertiwi University during the English-Indonesian translation process. Employing a descriptive research method, the investigation focuses on identifying and analyzing challenges encountered in translation. Participants, referred to as student translators, engaged in a translation test utilizing an English historical recount text. The test aimed to assess translation difficulties and was augmented by Translog, offering detailed insights into the process. Results reveal challenges encompassing lexical-semantic, grammatical, pragmatic, rhetorical, and cultural aspects. Lexical-semantic hurdles involve understanding word meanings and contextual relations, while grammatical challenges span handling idioms and addressing words with multiple meanings. Pragmatic issues delve into speaker intentions, contextual meanings, and socio-cultural considerations. Rhetorical challenges focus on translating figurative language, and cultural problems highlight expressing specific concepts in different cultures